Factors Affecting Employees' Performance: A Study Among Employees Of Telekom Malaysia, Pulau Pinang - Ismail, Ahmad (2001)
The fisrt part of this study measures the perception values of employees on individual, group and organizational-levels factors in relation to complaints received. The second part of the study probes at the relationships between and withion these levels.